Rina; THE CORRELATION BETWEEN TEACHER TEACHING SKILL PERCEPTION WITH THE STUDENTS’ MOTIVATION OF LEARNING JAPANESE AT MAN 2 SEMARANG - Alaviah, Rina; Oesman, Andy Moorad; Wardhana, Chevy Kusumah (Chi'e: Journal of Japanese Learning and Teaching, 2017)
Abstrak Keterampilan mengajar guru merupakan kecakapan atau  kemampuan seorang  guru  dalam  melaksanakan  dan  mengelola  kelas  dalam  proses kegiatan belajar mengajar. Oleh karena itu, keterampilan mengajar harus ada pada diri seorang guru.  Apabila  guru  tidak  memiliki  keterampilan  mengajar  maka pembelajaran  akan  kurang  efektif  dan  tujuan  belajar  tidak  dapat  tercapai dengan  maksimal. Keterampilan mengajar guru merupakan salah satu faktor yang mempengaruhi motivasi belajar siswa. Tujuan dari penelitian ini untuk mengetahui korelasi antara persepsi keterampilan mengajar guru dengan motivasi belajar bahasa Jepang siswa di MAN 2 Semarang. Jenis penelitian ini adalah deskriptif kuantitatif. Populasi penelitian adalah seluruh siswa kelas XII IPA dan XII IPS MAN 2 Semarang. Sampel penelitian adalah siswa kelas XII IPA 4 dan XII IPS 1. Instrumen yang digunakan adalah lembar angket. Data dianalisis dengan rumus product moment. Hasil penelitian menunjukkan bahwa terdapat hubungan positif yang kuat antara variabel X (persepsi keterampilan mengajar guru) dan variabel Y (faktor - faktor motivasi belajar siswa). Hal ini ditunjukkan melalui uji korelasi. Dalam uji korelasi, nilai r hitung adalah 0,6129  jika ditafsirkan dengan tabel penafsiran angka korelasi termasuk ke dalam kategori kuat. Sedangkan r tabel adalah 0,232 (5%) dan 0,302 (1%). Karena nilai r tabel lebih kecil daripada r hitung, maka disimpulkan terdapat korelasi positif yang kuat. Dengan demikian hipotesis satu (H1) dalam penelitian ini diterima dan secara otomatis hipotesis nol (H0) ditolak.   Abstract   The teachers’ teaching skill is an efficiency or ability of a teacher when doing and arranging the class in the process of teaching and learning activity. So, the ability of teaching has to be in a teacher.  While the teacher does  not have the ability of teaching, the activity of learning will not be effective and the aim of learning can not be achieved maximally. The teachers’ teaching ability is one of the factor that influence the students’ learning motivation. The aim of this research is to know the correlation between the perception of  teachers’ teaching ability with the students’ motivation in learning Japanese at MAN 2 Semarang. This kind of research is descriptive quantitative. The population of the research are all of  the students of XII grade in Science and Social Class at MAN 2 Semarang. The sample of the research are students of XII Science 4 and XII Social 1 grade. The instrument used is questionnaire. The data analysis using product moment formula. From the result of the research showing that there is the strong positive relation between X variable (the perception of teachers’ teaching ability) with Y variable (the factors of students’ learning motivation). It is shown through the correlation test. In correlation test, the value of r is counted 0.6129 if it is interpreted to the table of correlation number interpretation include in the strong category. While r table is 0,232 (5%) and 0.302 (1%). Because of the value of r is smaller than r count, so it can be concluded thet there is strong  positive  correlation.  So that the first hypothesis (H1) in the research is accepted and the zero hypothesis is rejected automatically.